ICT SECTOR ECONOMIC INDICATORS USING IO TABLE ANALYSIS DURING BIG DATA ERA - Rudi Rusdiah (Business and Entrepreneurial Review, 2015)
The purpose of this research is to analyze the impact of Imvestment toward economic indicator components of particular sector, to show how strategic BPS IO Table part of structured Big Data. ICT Service Sector was selected as one of the most impacted sector by massive data growth during Big Data era using economic indicatorssuch as Import; Indirect Tax; Labor Absorption. The model proposed by this research was based on IO Table Matrix using Leontief Ground theory; The methodology of this research was by constructing propositions from Leontief Inverse formula. This research data used secondary IO Table Matrix 36x36 from BPS (Indonesia Central Statistic Board) IO Table 175x175 (2008) updated. In addtion, by performing Forward and Backward linkage analysis. This research was limited to ICT Service Sector (31) of IO Table 36x36 Matrixes for period of 2009-2013, updates from BPS IO Table (2008). Nowadays, Practical and Managerial Implication shows that Industry Stakeholders in ICT Sector can have sovereignty and independent economic indicators optained such as Import; Indirect Tax; and Labor Absorption made available from local BPS IO Table.